(untitled) (Journal of Mathematical Study, 2021)
In this paper we consider a spectral problem which describes bending vibrations of a homogeneous rod, in cross-sections of which the longitudinal force acts, the left end of which is fixed rigidly and on the right end is concentrated an elastically fixed load. We study the uniform convergence of spectral expansions in terms of root functions of this problem.